Application of a Fenton process for the pretreatment of an iron-containing oily sludge: A sustainable management for refinery wastes. (15th February 2022) - Jerez, S.; Ventura, M.; Molina, R.; Martínez, F.; Pariente, M.I.; Melero, J.A.
Abstract: The feasibility of a Fenton-type process for the pretreatment of an oily refinery sludge has been explored taking advantage of the iron contained in the own sludge. This process reduces the content of total petroleum hydrocarbons (TPHs) accompanied by an increase in the total organic carbon concentration in the liquid phase. The effect of the temperature and the hydrogen peroxide loading was thoroughly studied in this work being the oxidant concentration the most critical parameter. Under 60 °C and 90 g/L of initial hydrogen peroxide concentration, the Total Organic Carbon (TOC) of the liquid phase was increased up values of 1336 mg/L and with a remarkable contribution of acetic acid as final oxidized compound (396 mgC/L). Additionally, nitrogen and phosphorous compounds were also dissolved in the aqueous phase achieving values of 250 mg/L and 7 mg/L for total Kjeldahl nitrogen and total phosphorous, respectively. Respirometry assays of the aqueous phase after the Fenton pretreatment have evidenced an increase of biodegradability up to 49% which makes this phase suitable for further biological processing in the refinery scheme. The reduction of the content of TPHs (61%) of the oily sludge, has also improved the settleability of the treated effluent (reducing the capillary suction time (CST) in ca. 88%). Graphical abstract: Image 1 Highlights: The best conditions were 90 g/L of H2 O2 and 60 °C using the own iron of the sludge. Fenton treatment yield a reduction of 61% of the TPHs of the oily sludge. The biodegradability of the aqueous phase was enhanced from 18% to 49%. The treatment breaks down the oil-water emulsion and improves the phases separation.